EXPERIMENTAL INVESTIGATION OF THE TENSILE CHARACTERISTICS OF SHOT PEENING FOR ALUMINUM METAL COMPOSITES (Jurnal Teknologi (Sciences & Engineering), 2025)
In recent years, obtaining new lightweight metals has become a requirement in addition to good mechanical properties for various uses. Metal matrix composites (MMCs) are materials that are manufactured by adding fibers or particles to enhance and support their properties. Aluminum alloys are used in various fields of engineering, aerospace, automobile, and construction industries. However, they have peer wear resistance due to their low hardness compared to metal matrices. Using matrix composites with aluminum- as a base material reinforcement with silicon carbide, eggshell, and zirconium oxide improved mechanical strength and usability. The current research investigates the mechanical properties of aluminum reinforced with SiC, ZrO2, and eggshell particles. Recycled aluminum is manufactured using stir casting with the addition of silicon carbide, eggshell, or zirconium oxide at a rate of 5% each. The samples were divided into four groups to study the mechanical properties before and after shot peening. Using the finite element method, all samples were analyzed by utilizing Abaqus 2022 programming to compare experimental and analytical results.  The results detected that the strength value for the AlZrO2 sample was the highest, and the second value of the tensile strength was with the specimen of (Sic). The lowest strength value was monitored at eggshell samples. These values were 91.54 MPa for AlZrO2, while it was 49 MPa for eggshells. The effect of the exposure time of shot peening at samples is direct, and their strength values increase when holding time increases.